RESOLUSI KONFLIKTERHADAP PERISTIWA KEKERASAN STRUKTURAL DI KELURAHAN BARA- BARAYA, KOTA MAKASAR, PROVINSI SULAWESI SELATAN - Adi, Luthfi Kalbu (Jurnal Idea Hukum, 2020)
The Indonesian National Army (TNI) has obligation to carry out its duties andfunctions to protect the honour and sovereignty of the Unitary Republic of Indonesia from other countries’ aggression. It rigidly containes in the TNI Law and its derivatives. But in some areas, TNI contributes to be one of the parties who involves in a conflict. Instead of mediating, its presence actually shows preference to one of the side including the conflict in Bara Baraya, Makassar. TNI is at the forefront in the process of evicting in the former housing complex of KODAM XIV Wirabuana/ Hasanuddin. Inevitably, in the end it provoked a backlash from local residents. This incident lefts a number of irregularities: (1) TNI does not have authority as a law enforcement apparatus (2) Execution of settlements is not based on any court decision. The method used in this research is sociological juridical research. Sources of legal material contained in this study from primary, secondary and tertiary legal materials with data collection techniques based on in-depth interviews and literature studies which  processed and analyzed by descriptive analysis methods. Based on the results of the study, it was found that there are two triggering factors that often cause conflicts in South Sulawesi, namely strategic location factors and  economic and cultural values of the Makassar people who are uncompromising when facing issues related to self-esteem. Methods of settlement which tend to be authoritarian, place the community in unequal position. Of course, in turn, the problems that began with civil disputes, expanded into structural conflicts. It should be that each party voluntarily is willing to think in an equal position and let go of each other's selfishness in order to create a pattern of resolution that is not only acceptable, but also lasts for a long period of time.